SOSIALISASI MENGENAI KETEPATAN KODEFIKASI DIAGNOSIS - Alfita Dewi; Ilma Nuria Sulrieni; Masdalena Masdalena; Suci Ramadhani (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
The Community Service (PKM) activity aims to provide knowledge to medical records staff, especially at the Belimbing Community Health Center, regarding the importance of accurate diagnosis coding to support data accuracy and the validity of health reports. Accurate diagnosis coding is the process of determining standard codes (usually ICD-10) that are accurate and appropriate to the patient's medical condition, which is very important for the quality of medical records, billing (INA-CBGs), health data analysis, and the quality of hospital services. The results of the activity showed that medical records staff were very enthusiastic when given socialization regarding the importance of accurate diagnosis coding. In conclusion, the Rules and Procedures for Diagnosis Coding at the Belimbing Community Health Center in Padang are not fully in accordance with the regulations of the Minister of Health No. 24 of 2022, because the implementation is still carried out by nurses, not medical record staff who have competence in this field. The main factors causing inaccurate coding are the incompatibility of task implementers with qualifications, lack of technical training, the unavailability of special SOPs, and minimal understanding of the use of the e-Puskesmas system and ICD-10